LINE INSPECTION ROBOT AND SYSTEM - BARTLETT GLYNN R; PHILLIPS ANDREW JOHN; MAJOR MARK (2012)
The present invention relates to an overhead transmission line inspection robot and system for inspecting transmission line components and right of way conditions. The overhead transmission line inspection robot includes a communications and control system adapted to control the robot and transmit information and a drive system for propelling the robot along a shield wire to enable inspection over a large area. The robot further includes a camera adapted to inspect right of way and component conditions; a light detection and ranging (LiDar) sensor adapted to measure conductor position, vegetation, and nearby structures; and a global positioning system adapted to identify the robot's position and speed.